Psychological reconstruction of female self-identity in the range of late maturity age crisis - Chyzhyk , Kateryna (Psychological Prospects Journal, 2020)
Purpose. The article is devoted to the theoretical grounding of female self-identity in the range of late maturity age crisis. The aim of the presented material is the theoretical explication of specificity of female self-identity in the range of late maturity age crisis utilizing reconstruction of “cognitive space” of the studied phenomenon.Methods. The method of psychological reconstruction lies as the basis of the theoretical study of the semantic and structural architectonics of the phenomenon of female self-identity that procedurally contributes to singling out formal and logical features of the studied phenomenon within female late maturity age crisis.Results. The results include the theoretical analysis of the basic positions of studying the range of late maturity age crisis of a woman and becoming specificity of her self-identity as a formed sense of personality determination and self-realization. The eclectic approach to the interpretation of the stated problem makes it possible to combine the diversity of “cognitive space” of female self-identity and the experience of late maturity crisis in the scheme of psychological reconstruction of their interrelation. Biological and psychosocial levels of female identity caused by convergence mechanism of functioning have been detailed; the variants of late maturity crisis passing in the forms of physical emancipation and synergy of “self-acquisition” have been determined, functioning under the influence of the convergence mechanism.Conclusions. The conclusions state the “cognitive completeness” of psychological reconstruction of the interrelation between female self-identity and late maturity crisis experience, which can be successfully realized in applied human research in involutionary period of its development.